A Multicentre, Observational Study of Sodium Picosulfate and Magnesium Citrate as a Precolonoscopy Bowel Preparation. (2009) - Love, Jonathan; Bernard, Edmond-Jean; Cockeram, Alan; Cohen, Lawrence; Fishman, Martin; Gray, James; Morgan, David
Abstract : BACKGROUND: Sodium picosulfate with magnesium citrate (PSMC) has been available as a precolonoscopy bowel preparation in Canada since 2005. A high patient acceptability and preference appears to have contributed to its wide adoption across the country. Despite its frequent use, there are relatively few published studies of this product, especially reports regarding its use in routine clinical practice. Moreover, to date, there have been no Canadian studies of any kind. OBJECTIVE: To conduct a preliminary evaluation of PSMC by prospectively collecting data describing its effectiveness. METHODS: In the present multicentre, observational study, sequential patients used PSMC according to each institution's standard colonoscopy protocol. Differences in bowel cleansing protocols included dose timing, fluid intake, dietary restrictions and administration of bisacodyl. During colonoscopy, preparation quality was rated separately for the right and left sides of the colon. RESULTS: Of the 613 patients entered, 606 were evaluable for efficacy. For the right and left colon, respectively, 93.0% and 96.2% of preparations were rated either 'excellent' or 'adequate'. In the 334 patients who received adjunctive bisacodyl and the 272 patients who did not, the results were similar: for the right and left colon, 92.3% and 97.1% of those who did not, and 93.4% and 95.7% of those who did receive bisacodyl, respectively, were rated either 'excellent' or 'adequate'. CONCLUSIONS: Despite the differences in bowel cleansing protocols used at each hospital (including an additional laxative), PSMC consistently yielded a high percentage of positive ratings for efficacy.